Internalizing Profiles of Homeless Adults: Investigating Links Between Perceived Ostracism and Need-Threat - Van Zalk, Nejra; Smith, Rebecca (Frontiers in Psychology, 2019)
Social ostracism among the homeless is a prevailing problem, yet few studies have focused on whether internalizing psychopathology moderates the links between feeling ostracized and perceiving threats to fundamental human needs. This study used a person-oriented approach to identify commonly occurring profiles of internalizing psychopathology characterized by symptoms of social anxiety, generalized anxiety, and depression (Low, Medium, and High Internalizers) among homeless participants residing in London, United Kingdom (N = 114; age range = 18–74; Mage = 46; 25% women). Data on perceived ostracism (feeling ignored and daily discrimination) and need-threat (belonging, self-esteem, meaningful existence, and feelings of control) was also collected. Controlling for the effects of age, living arrangement, gender, and time being homeless, feeling ignored was a significant predictor of need-threat, whereas daily discrimination was not. One significant interaction on the links between daily discrimination and need-threat emerged between Low and Medium Internalizers. For Medium Internalizers, high levels of daily discrimination were associated with high levels of need-threat. The effect was similar for High Internalizers and the opposite for Low Internalizers, though it was not significant within those groups. Taken together, these results indicate that differences in patterns of internalizing psychopathology should be taken into account when attempting to make homeless individuals feel more included in their surroundings.